Function of Renal Sympathetic Nerves - Yutang Wang (Frontiers Research Topics, 2017)
Sympathetic overactivity is associated with the development of hypertension. Renal denervation (RDN) prevents or delays hypertension in a variety of animal models, which laid the groundwork for the introduction of RDN as a clinical therapy in humans. In 2007, a novel, minimally invasive RDN ablation catheter was first trialled in hypertensive patients, with a 93% success rate of lowering blood pressure for at least three years post-RDN. However, a large scale, sham-controlled clinical trial (Symplicity HTN -3) failed to show reductions in BP greater than sham. The aim of this research topic was to evaluate the efficacy and safety of RDN, to explore the contribution of both afferent and efferent renal nerve activity to hypertension and non-hypertension disorders, and to stimulate future research to better understand the function of the renal nerves and the effects of RDN by highlighting gaps in knowledge.